2014
DOI: 10.1536/ihj.14-057
|View full text |Cite
|
Sign up to set email alerts
|

Etiology and Clinical Implications of Microvascular Dysfunction in Patients With Acute Myocardial Infarction

Abstract: SummaryIn patients with acute myocardial infarction (MI), coronary microvasculatures are often damaged irreversibly due to myocardial ischemia and reperfusion, and fl ow to the previously ischemic myocardium is markedly reduced, a phenomenon known as the "no-refl ow phenomenon". Percutaneous coronary intervention (PCI) may accelerate embolization of plaque gruels and microthrombi to the microvessels, which further reduces tissue perfusion. The extent of the no-refl ow zone correlates with infarct size, and it … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 42 publications
(47 reference statements)
0
17
0
Order By: Relevance
“…This occurs in up to 55% of patients following PCI and portends poor clinical outcome (Kloner et al 1974; van Kranenburg et al 2014; Wu et al 1998). MVO, largely caused by obstruction of the microcirculation with atherothrombotic debris, results in local inflammation, platelet aggregation, myocardial edema due to dysfunctional endothelium, and formation of in situ microvascular thrombi (Ito 2014; Robbers et al 2013). While many preventative and curative strategies have been employed (Bernink et al 2014; Fröhlich et al 2013; Galasso et al 2014), there has been no consistently efficacious therapeutic approach.…”
Section: Introductionmentioning
confidence: 99%
“…This occurs in up to 55% of patients following PCI and portends poor clinical outcome (Kloner et al 1974; van Kranenburg et al 2014; Wu et al 1998). MVO, largely caused by obstruction of the microcirculation with atherothrombotic debris, results in local inflammation, platelet aggregation, myocardial edema due to dysfunctional endothelium, and formation of in situ microvascular thrombi (Ito 2014; Robbers et al 2013). While many preventative and curative strategies have been employed (Bernink et al 2014; Fröhlich et al 2013; Galasso et al 2014), there has been no consistently efficacious therapeutic approach.…”
Section: Introductionmentioning
confidence: 99%
“…17) Recently, it has been reported that reducing the door-toballoon time is not sufficient for in-hospital mortality. 26,27) We may pay more attention to pre-hospital activity such as first medical contact (FMC) to balloon time. There were 55 cases of suspected AMI for which our Doctor Car was required.…”
Section: Discussionmentioning
confidence: 99%
“…33) NICO has both ATP-sensitive KATP channel opener and nitrate properties, and it has a protective effect on myocardial I/R injury in animal models 10,11) and humans. [34][35][36] Ishii, et al 37) reported in a randomized study that the addition of intravenous NICO to percutaneous coronary intervention prevented cardiovascular events in patients with acute myocardial infarction, although NICO did not limit infact size in a multicenter study that was performed using a lower dose of NICO compared to a previous study.…”
Section: Effect Of Interstitial Ne Concentration On Ischemiareperfusimentioning
confidence: 97%